Literature Review : Pengaruh Pendidikan Seksual Orang Tua Pada Anak Usia Dini Terhadap Kejadian Sexual Abuse - Nunung - hasanah; Tuti Suryani; Sudirman Sudirman (LPPM UNIKAL, 2023)
Sexual education is teaching given by parents to their children so that a child can prevent sexual violence from being suspected of occurring. This study aims to determine the effect of parental sexual education in early childhood on the incidence of sexual abuse. The research method used the literature review method, which was traced using the Google Scholar, PubMed, and ProQuest (2016-2021) databases which found 11 journals. Results from all journals reviewed, it shows that there is an effect of parental sexual education in early childhood on the incidence of sexual abuse. Keyword : Education, Sexual, Parents, Early Childhood, Sexual Abuse